Migration and Culture - Gil S. Epstein; Ira N. Gang (Institute for the Study of Labor (IZA), 2010)
Culture is not new to the study of migration. It has lurked beneath the surface for some time, occasionally protruding openly into the discussion, usually under some pseudonym. The authors bring culture into the open. They are concerned with how culture manifests itself in the migration process for three groups of actors: the migrants, those remaining in the sending areas, and people already living in the recipient locations. The topics vary widely. What unites the authors is an understanding that though actors behave differently, within a group there are economically important shared beliefs (customs, values, attitudes, etc.), which we commonly refer to as culture. Culture and identify play a central role in our understanding of migration as an economic phenomenon; but what about them matters? Properly, we should be looking at the determinants of identity and the determinants of culture (prices and incomes, broadly defined). But this is not what is done. Usually identity and culture appear in economics articles as a black box. Here we try to begin to break open the black box.
urn:nbn:de:101:1-201010132783
Keywords: R23; O15; F22; 330; migration; culture